Strategi Guru Untuk Meningkatkan Kemampuan Membaca Permulaan Pada Siswa Kelas I SD di Masa Pandemi - Ilman Hanafi Destian; Dwiana Asih Wiranti; Aan Widiyono (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The ability to read is one of the aspects of language that students in elementary school need to learn. The success of students in learning is influenced by the mastery of students' reading skills at the beginning level. The impact of the Covid-19 virus makes it difficult for grade 1 elementary school students to read so that they have difficulty understanding the material presented by the teacher through online learning. For this reason, steps were taken to implement the strategy by holding "Reading Lessons". Through this strategy, it is hoped that: 1) the students' initial reading ability will increase; 2) understand the supporting and inhibiting factors of teachers in implementing strategies to improve students' early reading skills. The research design used descriptive qualitative. The research subjects were teachers and first grade students of SDN 1 Bawu Jepara. Data collection techniques using observation, interviews, and documentation. Data analysis through data reduction, data presentation, and drawing conclusions. The results showed that: 1) the "Les Reading" strategy can improve students' initial reading skills through: a) planning (teacher preparation in delivering materials and using learning methods and media; b) implementing strategies (learning steps and student participation); and 2) The supporting factors for the strategy are parents, school policies, and the availability of learning media. While the inhibiting factors for the strategy are internal to the students and the limited time for implementation.